2014
DOI: 10.5978/islsm.14-or-02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stress-free Therapy on Cerebral Blood Flow: Comparisons among patients with metabolic cardiovascular disease, healthy subjects and placebo-treated subjects

Abstract: We have developed a novel Stress-free Therapy ® wherein Pinpoint Plantar Long-wavelength Infrared Light Irradiation (PP-LILI) increases peripheral-deep body temperature and blood flow volume and stabilizes blood pressure as well as significantly reduces stress hormones such as adrenocorticotropic hormone (ACTH) and cortisol without using drugs. Furthermore, we demonstrated that this therapeutic method significantly improves blood glucose and insulin resistance in patients with type 2 diabetes. 1, 2) Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…We previously reported that pinpoint plantar long-wavelength infrared light irradiation (stress-free therapy; SFT) suppresses the stress reaction mediated by cortisol and contributes to alleviation of insulin resistance and elevation of intracranial blood flow in patients with type 2 DM. 5 , 6 , 7 , 8 We have additionally demonstrated that SFT activates the immunoresponsive CD19 + CD24hi and CD38hi B-reg cell groups and induces the expression of IL-10 on lymphocytes. 9 …”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…We previously reported that pinpoint plantar long-wavelength infrared light irradiation (stress-free therapy; SFT) suppresses the stress reaction mediated by cortisol and contributes to alleviation of insulin resistance and elevation of intracranial blood flow in patients with type 2 DM. 5 , 6 , 7 , 8 We have additionally demonstrated that SFT activates the immunoresponsive CD19 + CD24hi and CD38hi B-reg cell groups and induces the expression of IL-10 on lymphocytes. 9 …”
Section: Introductionmentioning
confidence: 70%
“…3 , 11 SFT has already demonstrated efficacy in alleviating DM and dementia and is expected to be useful for preventing Sdiabetes-related dementia by alleviating insulin resistance and increasing intracranial blood flow. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that pinpoint plantar longwavelength infrared light irradiation (PP-LILI) stimuli normalizes blood flow and pressure, suppresses ACTH and cortisol levels and improves type II diabetes [1][2][3] . All these evidences suggested that PP-LILI stimuli affect systemic homeostasis and thus it was thought that the stimuli also affect immune system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the developmental environment in the juvenile stage is considered one of the pathogenetic factors of mental disease, and rodents reared in isolation for a long time in the juvenile stage serve as important model animals . Rearing small laboratory animals such as mice and rats individually for a long time leads to behavioral changes not seen in group‐reared normal animals, called “isolation syndrome” , which includes anxiety, depression, increased aggression, and memory disorder . Isolation syndrome is used as a model for human mental diseases such as schizophrenia, anxiety disorder, mood disorder, and drug dependence .…”
Section: Introductionmentioning
confidence: 99%